Multimodal cues facilitate nest recognition in carpenter bee aggregations. (September 2019) - Ostwald, Madeleine M.; Shaffer, Zachary; Pratt, Stephen C.; Fewell, Jennifer H.
Abstract : The advantages of group living are partially offset by the cognitive challenges associated with maintaining social boundaries. These challenges can give rise to recognition mechanisms that adaptively integrate information across multiple sensory modalities. The valley carpenter bee, Xylocopa varipuncta, nests in dead wood in large aggregations of up to several dozen nests. This study investigates the proximate mechanisms by which returning foragers quickly and reliably identify their own nest entrance within a high-density nesting site. We manipulated long- and short-range visual cues associated with nest entrances, removed chemical cues on the inside of nest entrances and added chemical cues from foreign conspecific bees. By measuring the effect of these manipulations on nest search time and search accuracy, we assessed the importance of visual and olfactory sensory modalities in allowing carpenter bees to locate their nests within aggregations. Our results support the hypothesis that both visual and olfactory cues can facilitate nest localization. Removal of nest olfactory cues did not significantly disrupt homing, suggesting that olfactory information may not be necessary for nest localization when visual information is available. However, the addition of olfactory cues from unfamiliar conspecific bees actually aided nest localization rather than disrupting it, suggesting that bees may use generalized species odour cues for homing. Due to intense nest site competition within aggregations, nest localization may have important social implications for maintenance of high-density nesting. Highlights: Carpenter bees navigate to their nest entrances using visual and olfactory cues. Returning foragers use both proximal and distal visual cues. Odour cues from foreign bees assist in nest localization.